2017
DOI: 10.15567/mljekarstvo.2017.0204
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and milk fatty acid composition as a response to dietary n-3 fatty acids and selenium in periparturient Holstein cows

Abstract: Linseed is well known for abundant content of α-linolenic acid why it has been widely used as a source of n-3 fatty acid. Higher ratio of polyunsaturated fatty acids can increase lipid peroxidation. Selenium (Se) plays a key role in antioxidant enzymes and can therefore be regarded for use in attempts focused on protection of fatty acids from oxidation. The organic Se has been shown to have higher bioavailability compared to the inorganic selenium. The aim of this research was to determine the influence of die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…5,10,11 Conversely, Se supplementation in animal nutrition contributes to increased feed intake and subsequent daily weight gain, 12,13 crucial factors in beef cattle raising. Moreover, Đidara et al 14 reported the positive effects of organic Se supplementation in the diet of dairy cattle, resulting in higher levels of omega-3 fatty acids in milk.…”
Section: Introductionmentioning
confidence: 99%
“…5,10,11 Conversely, Se supplementation in animal nutrition contributes to increased feed intake and subsequent daily weight gain, 12,13 crucial factors in beef cattle raising. Moreover, Đidara et al 14 reported the positive effects of organic Se supplementation in the diet of dairy cattle, resulting in higher levels of omega-3 fatty acids in milk.…”
Section: Introductionmentioning
confidence: 99%